Women Overestimate Temporal Duration: Evidence from Chinese Emotional Words - Zhang, Mingming; Zhang, Lingcong; Yu, Yibing; Liu, Tiantian; Luo, Wenbo (Frontiers in Psychology, 2017)
Numerous studies have proven the effect of emotion on temporal perception, using various emotional stimuli. However, research investigating this issue from the lexicosemantic perspective and gender difference remains scarce. In this study, participants were presented with different types of emotional words designed in classic temporal bisection tasks. In Experiment 1 where the arousal level of emotional words was controlled, no pure effect of valence on temporal perception was found; however, we observed the overestimation of females relative to males. Furthermore, in Experiment 2, an orthogonal design of valence and arousal with neutral condition was employed to study the arousal-mechanism of temporal distortion effect and its difference between genders. The results showed that the gender difference observed in Experiment 1 was robust and was not influenced by valence and arousal. Taken together, our findings suggest a stable gender difference in the temporal perception of semantic stimuli, which might be related to some intrinsic properties of linguistic stimuli and sex differences in brain structure as well as physiological features.